The Effect of Sensory Marketing on the Purchase Behavior of Sports Wear Products - Remziye Kartop; Özlem Ekizoğlu (Journal of Educational Issues, 2024)
Intense competition conditions push businesses and brands to differentiate. One of the ways brands differentiate themselves from their competitors is to carry out interesting marketing activities for consumers. In this sense, sense-oriented marketing strategies can be used to activate the purchasing behavior of consumers. This research aims to reveal how consumers are affected by sensory marketing elements when purchasing sports ready-to-wear products and their differences according to demographic characteristics. Tekin (2021) used the scale of “the effect of sensory marketing on the buying behavior of ready-made clothing”, which he used in his graduate study. The sample group consists of 241 female and 259 male participants who volunteered and visited the sports shops of 6 shopping centers in Istanbul. In the analysis of the data, Multiple Frequency, Mann-Whitney U test and Kruskal Wallis analyzes were applied. It is seen that men, participants with university education, 34-41 age group and 2501-4000 TL monthly income spend more in the consumption of sports textile products. The participants stated that they purchase 10% or less of their monthly budget for sports products, they mostly buy from the physical store, they prefer classical music in the store, they show more demand for light colored products, and the majority prefer the Adidas brand. The effect of visual, olfactory and tactile stimuli in the store atmosphere on the consumption of sports textile products, on gender and education; visuality of brand and store design on gender, education and monthly income; It has been determined that olfactory and auditory stimuli show significant differences according to education and monthly income. It is seen that the effect of product visualization and the effect of olfactory, auditory and tactile stimuli do not change according to any personal characteristics.